Correction: Emerging investigators series: comparing the inherent reactivity of often-overlooked aqueous chlorinating and brominating agents toward salicylic acid. Issue 5 (18th April 2018) - Broadwater, Matthew A.; Swanson, Tyler L.; Sivey, John D.
Abstract : Correction for 'Emerging investigators series: comparing the inherent reactivity of often-overlooked aqueous chlorinating and brominating agents toward salicylic acid' by Matthew A. Broadwater et al., Environ. Sci.: Water Res. Technol., 2018, 4, 369–384.